Dr. Damian Marucci — Deep Plane Facelift — Sydney - Marucci, Damian (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Damian Marucci, practicing in Sydney, Australia. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003269; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; australia; sydney